(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This article presents the results of scientific research carried out today on one of the main tasks of reforms in the cotton sector, further improving the quality and yield of cotton raw materials, increasing the volume of high and high-quality seed production, improving fiber quality and output, and finding a solution to the issues of rational use of land and Water Resources.